A Sectoral Analysis of Price-Setting Behavior in U.S. Manufacturing Industries - Leith, Campbell; Malley, Jim (The Review of Economics and Statistics, 2007)
In this paper we estimate New Keynesian Phillips curves (NKPC) for U.S. manufacturing industries defined at the SIC two digit level over the period 1959 to 1996. This enables us to measure the extent of nominal inertia across industrial sectors. A key innovation in this research is the use of intermediate-goods costs rather than labor costs as a measure of marginal costs. Intermediate-goods costs are a more significant element of costs for the firms populating our sample and are not subject to the criticism that wage rates are nonallocative. We find that there is statistically significant variability in estimates of price stickiness, ranging from eight months to two years. We also find that estimates of backward-looking price-setting behavior vary, with some industries characterized by 81% of pricing decisions made in a purely forward-looking manner, while in others only 52% of pricing decisions are made that way. Market concentration (as captured by the Herfindahl-Hirschman index) appears to be associated with increased price stickiness, but reduced rule-of-thumb behavior, in setting prices. Finally, firms are also more likely to follow simple rules of thumb when output in their industry is more volatile.